Improving schools using systems leadership : turning intention into reality - Macdonald, Ian, 1950 October 23-; Dixon, Clive, 1956-; Tiplady, Tony (Routledge, 2019)
It is easy to underestimate the impact that school organisation has on the behaviour, effectiveness, engagement and creativity of the teachers, staff and students who work within it. It also has a marked effect on the well-being of staff members, and how families and the community relate to the school. Attempts to improve school organisation are often short term "initiatives" that only cover only one or two aspects of what it takes to organise a school effectively. Improving Schools Using Systems Leadership, in contrast, provides those involved in the design and delivery of educational services with a coherent and easy-to-follow framework to help run an effective organisation. Based on theory, real data on education improvements at school and regional level, and case studies, this book demonstrates how Systems Leadership can be used to improve school organisation. It integrates models of leadership, teamwork, capability, structure and systems to help make them more effective in improving the learning outcomes of students and also sustain this improvement over time. This book explains how Systems Leadership can and has been applied in schools to bring clarity to the purpose, structure and systems within a school and have a major impact on its success. As such, it is an essential text for school leaders and managers looking for practical tools to help improve the working lives of the people within their organisation, and hence their effectiveness.- Resumé vydavatel